Does Democracy Make Taller Men? Cross-Country European Evidence - Alberto Batinti; Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study whether a democracy improves a measure of individual wellbeing; human heights. Drawing on individual-level datasets, we test the hypothesis using a battery of eight different measures of democracy and derived averages, and include models accounting for several confounders, regional and cohort fixed effects. We document that democracy - or its quality during early childhood - shows a strong and positive conditional correlation with male, but not female, adult stature. Our preferred estimates suggest that being born in a democracy increases average male stature from a minimum of 1.33 to a maximum of 2.4 cm. Together with the positive association with male stature and the increase in gender dimorphism, we also show an additional contribution when democracy increases furtherly during adolescent years, and when we adopt measures of existing democratic capital before birth and at the end of height plasticity in early adulthood. We also find that democracy is associated with a reduction in inequality of heights distribution. We find period-heterogeneity in our results, with early democratizations being more effective on heights than later ones. Results are robust to the inclusion/exclusion of countries exposed to communism.
Keywords: I18; P20; 330; democracy; wellbeing; human heights; waves of democratisation; communism; Europe; survey data